Kyrgyz Republic : Fiscal Sustainability Study - World Bank (Washington, DC, 2013)
The study reviews the macroeconomic developments in the Kyrgyz Republic following the collapse of the Soviet Union, when adjustments were required since output fell by fifty percent between 1991-95, resulting in adverse fiscal consequences, which triggered losses in tax revenues, along with the implicit end of energy subsidies. Part I examines the fiscal, and debt sustainability, proposing a three-fold strategy: a) efforts for an urgent renewal are needed to consolidate macroeconomic stability -- fundamentally, a significant fiscal adjustment is required; b) debt relief should be considered, given the large burden, and there is the need to preserve social expenditures; and c) decisive structural reforms are necessary to underpin fiscal adjustment, and increase the efficiency of resource uses. Part II examines the structural issues, particularly the tax system, and the role of the state in infrastructure and utilities, focusing on accelerating the transformation of public infrastructure and utility companies, and how to improve taxation. The report also emphasizes a transparent and targeted system in the provision of basic services to the poor, through reform policies and the inclusion of the private sector.